1992
DOI: 10.1002/jez.1402610412
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphic vs. tissue regeneration in Xenopus forelimbs

Abstract: Postmetamorphic froglets of Xenopus laevis regenerate hypomorphic unbranched spikes from amputated arm stumps. These are composed primarily of cartilage, produced from blastemalike structures sparsely populated with cells and rich in connective tissue. Some consider these outgrowths to be an example of epimorphic regeneration produced from blastemas, albeit deficient ones. Others interpret them as a case of tissue regeneration derived from fibroblastemas augmented by chondrocytes and periosteal and perichondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…However, other regeneration biologists (Carlson, 1978(Carlson, , 2005Goss, 1980Goss, , 1983Goss, , 1984Reichman, 1984;Goss and Holt, 1992) do not use the term epimorphic regeneration in this broad sense, but apply a narrower (more specific) concept of this process. For these authors, epimorphic regeneration by definition involves the formation of a blastema composed of dedifferentiated cells.…”
Section: Antler Regeneration As An Epimorphic Processmentioning
confidence: 94%
“…However, other regeneration biologists (Carlson, 1978(Carlson, , 2005Goss, 1980Goss, , 1983Goss, , 1984Reichman, 1984;Goss and Holt, 1992) do not use the term epimorphic regeneration in this broad sense, but apply a narrower (more specific) concept of this process. For these authors, epimorphic regeneration by definition involves the formation of a blastema composed of dedifferentiated cells.…”
Section: Antler Regeneration As An Epimorphic Processmentioning
confidence: 94%
“…This contrasts with the situation in urodeles where a complete and correctly patterned limb is regrown: the textbook case of epimorphic regeneration (see Box 1 for definition). Grafting experiments performed by Goss and Holt in 1992 support the idea that epithelial-mesenchymal interactions are required for production of the hypomorphic spike (Goss and Holt, 1992). They showed that skinned forelimbs amputated at wrist level could not form a blastema when inserted into the abdominal cavity.…”
Section: Box 3: Post-metamorphic Limb Regeneration: Epimorphosis or Tmentioning
confidence: 95%
“…Indeed the mosaic behaviour of the chick limb bud was long held to represent evidence for the progress zone model (Summerbell et al 1973). However, like other anurans, and unlike urodele amphibians, Xenopus can produce only the occasional hypomorphic unbranched spike if amputated after metamorphosis (Goss & Holt 1992 One hundred per cent of complete regenerates can only be formed up to stage 52, when the developing limb is a flattened paddle shape, and the ability to regenerate a complete limb declines progressively until stage 57 when only the occasional toe is formed (Dent 1962). Although this ability is of some interest, it is not clear, prima facie, that it is really the same sort of phenomenon as regeneration of the urodele limb, which involves dedifferentiation of mature cells to form a blastema (Nye et al 2003).…”
Section: Limbmentioning
confidence: 99%